2019
DOI: 10.21475/ajcs.19.13.02.p1403
|View full text |Cite
|
Sign up to set email alerts
|

Association of biochemical traits with grain yield in triticale genotypes under normal irrigation and drought stress conditions

Abstract: Effectiveness of selection of high-yield genotypes under drought stress environments can be improved by using biochemical traits as indirect selection indicators. The objective of this study was to determine the extent to which biochemical traits are associated with triticale grain yield under normal irrigation and drought stress conditions. This field study was conducted to evaluate grain yield and various biochemical traits of 58 triticale genotypes during three consecutive growing seasons (2013-2016). Norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Consequently, our results showed the efficiency of heatmap analysis in screening and breeding programs and also showing a combination of relationships within features, genotypes, and cross relationships between features and genotypes. In accordance with our results regarding the importance of SOD activity, the relationship of biochemical features and grain yield of triticale was modeled in the study of Saed-Moucheshi [ 45 ], without estimation of their heritability and other genotypic parameters, and it showed that showed that MDH, proline contents and SOD were the important features with significant impacts on triticale grin yield. Similarly, Riasat et al [ 43 ] nominated SOD activity as the most appropriate trait to obtain higher tolerant triticale genotypes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consequently, our results showed the efficiency of heatmap analysis in screening and breeding programs and also showing a combination of relationships within features, genotypes, and cross relationships between features and genotypes. In accordance with our results regarding the importance of SOD activity, the relationship of biochemical features and grain yield of triticale was modeled in the study of Saed-Moucheshi [ 45 ], without estimation of their heritability and other genotypic parameters, and it showed that showed that MDH, proline contents and SOD were the important features with significant impacts on triticale grin yield. Similarly, Riasat et al [ 43 ] nominated SOD activity as the most appropriate trait to obtain higher tolerant triticale genotypes.…”
Section: Discussionsupporting
confidence: 81%
“…The obtained data related to field experiments were subjected to combined analysis of variance (combined ANOVA) and descriptive statistic’s, such as mean and standard error. After that, the mean squares (MS) obtained from combined ANOVA for each of normal irrigation and drought stressed trials were used for estimating the residual (res) variance, variance of block (blk) within year (yr), genotype (gn) by year variance, genotypic variance, environmental variance, phenotypic variance, broad sense (general) heritability, genotypic coefficient of variation (GCV), and phenotypic coefficient of variation (PCV) based on the following formulas [ 18 , 45 ]. Mean comparison based on LSD test ( p = 0.05) was carried out using MEANS statement in PROC GLM of SAS software.…”
Section: Methodsmentioning
confidence: 99%
“…However, in our experiment, we failed to find a relationship between the proline content in seedling shoots and their drought resistance under stress conditions. A negative correlation between the proline content and drought tolerance was also shown for triticale (Saed-Moucheshi et al, 2019). Despite the importance of proline as a multifunctional protector, a lower increase in its content under moderate stress may indicate a greater resistance of plants (Kuznetsov, Shevyakova, 1999).…”
Section: Discussionmentioning
confidence: 71%
“…These environmental strains cause enormous crop damage by decreasing yield by maximum 50% in various plant crops recognized to the increased reactive oxygen species (ROS) that induce oxidative stress in plants (Shafi et al, 2009). Environmental stresses decrease plant growth and development by affecting various physio organic mechanisms for example, hormonal indicating, antioxidant systems and photosynthesis (Jabeen et al, 2019;Saed-Moucheshi;. These abiotic stresses induce [ 142 ] compound responses in crop to inhibit growth and enhanced their survivability under drought stress situations.…”
Section: Introductionmentioning
confidence: 99%